Visual Contrast Processing is Largely Unaltered during Saccades - García-Pérez, Miguel A.; Peli, Eli (Frontiers in Psychology, 2011)
Saccadic suppression refers to a reduction in visual sensitivity during saccadic eye movements. This reduction is conventionally regarded as mediated by either of two sources. One is a simple passive process of motion smear during saccades also accompanied by visual masking exerted by high-contrast pre- and post-saccadic images. The other is an active process exerted by a neural mechanism that turns off visual processing so that the perception of a stable visual environment is not disrupted during saccades. Some studies have actually shown that contrast sensitivity is significantly lower during saccades than under fixation, but these experiments were not designed in a way that could weigh the differential contribution of active and passive sources of saccadic suppression. We report the results of measurements of psychometric functions for contrast detection using stimuli that are only visible during saccades, thus effectively isolating any visual processing that actually takes place during the saccades and also preventing any pre- and post-saccadic visual masking. We also report measurements of psychometric functions for detection under fixation for stimuli that are comparable in duration and spatio-temporal characteristics to the intrasaccadic retinal stimulus. Whether during saccades or under fixation, the psychometric functions for detection turned out to be very similar, leaving room only for a small amount of sensitivity reduction during saccades. This suggests that contrast processing is largely unaltered during saccades and, thus, that no neural mechanism seems to be actively involved in saccadic suppression.